2012
DOI: 10.1002/pc.22254
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial effects of natural phenolic compounds on green composite materials

Abstract: The aim of this study is to establish the thermal characteristics of a biocomposite (Arbofill kokos®), stabilized with different natural phenolic additives, in order to check the antioxidant capacity of the resulting compounds on the biocomposite. The phenolic compounds used were thymol, carvacrol, α-tocopherol and tannic acid, and the concentrations used were 0.5wt% and 2wt% of each compound. The results obtained were compared with the same biocomposite stabilized with an industrial antioxidant agent (octadec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In particular, some authors have reported similar results with other natural antioxidants [62,63]. For instance, España et al [64] showed that the incorporation of phenolic compounds successfully improved the T deg values of green composites made of a mixture of lignin and organic coconut fibers (CFs) with an excellent stabilization provided by tannic acid.…”
Section: Filmmentioning
confidence: 74%
“…In particular, some authors have reported similar results with other natural antioxidants [62,63]. For instance, España et al [64] showed that the incorporation of phenolic compounds successfully improved the T deg values of green composites made of a mixture of lignin and organic coconut fibers (CFs) with an excellent stabilization provided by tannic acid.…”
Section: Filmmentioning
confidence: 74%
“…Another study of a commercial lignin‐based material Arbofill kokos® containing short coconut fibers and 2% w/w thymol, a common AM agent, showed significant inhibition of Gram‐positive S. aureus after 20 h incubation although no AM activity against Gram‐negative bacteria, E. coli , was observed (España et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The melt stability of polyolefins has been widely studied by testing the typical thermal processing conditions controlling the melting atmosphere under limited oxygen . Several traditional synthetic antioxidants have been used as useful additives to protect the polymeric matrix during processing in really small amounts (i.e., between 0.1 and 0.3 wt%) . Most of the natural occurring antioxidants are polyphenolic compounds derived from flavonoids, which are gaining considerable interest in the plastic processing industry to replace the traditional synthetic antioxidants used for more environmental ones .…”
Section: Introductionmentioning
confidence: 99%
“…[8,15] Several traditional synthetic antioxidants have been used as useful additives to protect the polymeric matrix during processing in really small amounts (i.e., between 0.1 and 0.3 wt%). [16][17][18] Most of the natural occurring antioxidants are polyphenolic compounds derived from flavonoids, which are gaining considerable interest in the plastic processing industry to replace the traditional synthetic antioxidants used for more environmental ones. [8,9,13,14,16] For instance, Samper et al, processed PP with several NA and they demonstrated that flavonoids such as silibinin and quercetin provide better stabilizing effect to PP matrix than flavanone glycosides (i.e., hesperidin and naringin), providing stabilization effect similar to that provided by conventional petroleum-derived antioxidants, [14] typically used at industrial level, such as ethanox and Irganox.…”
Section: Introductionmentioning
confidence: 99%